Social Antecedents to the Development of Interoception: Attachment Related Processes Are Associated With Interoception - Oldroyd, Kristina; Pasupathi, Monisha; Wainryb, Cecilia (Frontiers in Psychology, 2019)
Current empirical work suggests that early social experiences could have a substantial impact on the areas of the brain responsible for representation of the body. In this context, one aspect of functioning that may be particularly susceptible to social experiences is interoception. Interoceptive functioning has been linked to several areas of the brain which show protracted post-natal development, thus leaving a substantial window of opportunity for environmental input to impact the development of the interoceptive network. We first introduce a biopsychosocial model of interoceptive development. In our proposed model of interoceptive development, attachment related processes are purported to affect the development of interoception by influencing the growth of neural architecture and by modifying functioning of the HPA axis. Further, the idea that patterns of caretaking affect children’s development of interoception is presented. This model explains both normatively developing interoception and accounts for instances in which dysfunctional attachment related processes can lead to either a hypersensitivity or a blunted awareness of bodily cues. Second, we report findings from two existing datasets showing significant relationships between attachment related processes and interoception. In the first study, looking at a sample of healthy young adults (n = 132, 66 males), we assessed self-reported interoceptive awareness and attachment style. We found relationships between aspects of interoception and attachment style such that avoidant individuals reported lower interoceptive functioning across several dimensions (r’s (130) = -.20 to -.26, p’s<.05). More anxious individuals, on the other hand, reported heightened interoceptive across several dimensions (r’s(130)=.18 to .43, p’s < .05). In the second study, we examined the congruence between a person’s self-reported negative emotion and a measure of sympathetic nervous system arousal (SCL). The congruence score was positively associated with parental rejection of negative emotion. These results suggest that parenting style, as reported by the mother, are associated with a child’s ability to coordinate their self-reported emotional and physiological responding across a series of independent assessments, r(108)= -.24, p<.05. In other words, the more maternal reported parental rejection of child negative emotions, the less congruent a child’s self and physiological reports of distress.